Successful use of brachytherapy for a severe hidradenitis suppurativa variant. Issue 6 (18th July 2016) - Paul, Suchismita; Bach, Daniel; LeBoeuf, Nicole R.; Devlin, Phillip M.; Lipworth, Adam D.
Abstract: Hidradenitis suppurativa is a member of the follicular occlusion tetrad, along with acne conglobata, dissecting cellulitis of the scalp and pilodinal sinus. These conditions share common pathophysiologic features, including follicle occlusion, bacterial overgrowth, severe suppurative inflammation, scarring, and sinus tract formation. Treatment of severe cases is challenging, and a novel treatment modality would be of significant value. We describe a 46‐year‐old man who presented with a 15‐year history of suppurative and scarring nodules involving his groin, scalp, neck, face, and chest. Based on their distribution and morphology, these lesions were most characteristic of hidradenitis suppurativa, although he had features of acne conglobata and dissecting cellulitis as well. Over the years, he had been treated with several antimicrobial and immunomodulatory agents, the main conventional therapies for follicular occlusion syndromes, without much success. We then treated him with superficial brachytherapy to his right groin and occiput, which led to significant improvement. No toxic side effects were noted. This case demonstrates the successful application of superficial brachytherapy for the treatment of severe hidradenitis suppurativa, and possibly for other follicular occlusion syndromes.